Cocoa Shell as a Bulking Agent in Nutritionally Improved Cocoa Spreads with Sugar Substitutes. - BARIŠIĆ, VERONIKA; AČKAR, ĐURĐICA; LONČAREVIĆ, IVANA; PETROVIĆ, JOVANA; BENŠIĆ, MIRTA; PAULIK, DANIELA; DOKO, KRISTINA; JOZINOVIĆ, ANTUN; BABIĆ, JURISLAV; ŠUBARIĆ, DRAGO; FLANJAK, IVANA (Current Research in Nutrition & Food Science, 2024)
Due to unhealthy lifestyle, Western countries are dealing with pandemic of overweight and obesity. To tackle the problem, industry has been looking for solutions to produce nutritionally improved foods. In the present research, sucrose was fully substituted with xylitol, or by combination of xylitol and stevia with cocoa shell as a bulking agent. Apart from reducing caloric value of the sweet spreads, protein, ash, methylxanthine and phenolic compound contents were increased, without major influence on fatty acid composition. The spreads with added cocoa shell may be declared as a source fibre. Although stability of sweet spreads during storage was not compromised, which is visible from low water activity (between 0.132 for control sample and 0.233 for sample with 52 % xylitol) and high colloidal stability (above 99), rheological properties and texture of the spreads deteriorated (increase of plastic viscosity from 3.708 Pas up to 18.280 Pas and decrease of spread ability from 1180.43 gs up to 334.670 gs), which could pose an issue from the technological and sensorial points of view. Overall, satisfactory products were obtained with potential for further upgrade for industrial production.